STUDY ON THE INFLUENCE OF WELDER’S FATIGUE ON THE QUALITY OF WELD LINES - DIANA LUNGU; ALEXANDRU ACSINTE; CAROL SCHNAKOVSZKY; EUGEN HERGHELEGIU; CRINA RADU (Journal of Engineering Studies and Research)
In this paper a case study is presented, based on certain exercises applied to different welders, to evaluate the influence of welder’s fatigue on the quality of welding. The performed test was aimed at evaluating the technical performance (the welding act) of subjects, as well as the accuracy of weld lines. Five modules of exercises were applied. The exercises of each module were various, they were of medium level, so that they were neither overburdened, nor unsolicited, because both situations could lead to accidents due to fatigue. A weld line was performed after each exercises’ module. The visual quality of welding was appreciated according to the EN ISO 17637:2011 standard.